Perceptions of the nursing job by young people of secondary school as a choice of future profession — preliminary study - Mędrzycka-Dąbrowska, Wioletta; Bąkowska, Grażyna; Kwiecień-Jaguś, Katarzyna; Gaworska-Krzemińska, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. The choice of study as well as future career is very important issue for every young people. The choice of the future profession should be deliberate choice of taking into account abilities and interests. Nursing profession is specific in many ways. Making a decision about being a nurse require constant readiness to help others and this is a value itself. Aim of the study. The aim of the study was to: examine perceptions of nursing as a career by young people of secondary school; diagnose what kind of factors influence their subsequent career decision either to choose or to reject nursing. Material and methods. The research group included 383 randomly selected participants from secondary school. Data was collected on the authorship questionnaire. The study was carried out from December 2010 to March 2011. Results and conclusions. The research showed that nursing profession, by majority of young people, was associated with: caring/helping people, high level of commitment and diligence. The study indicated that there is a substantial shortage in nursing profession and great need for education in this field. The main motives to choose nursing profession was: interesting and attractive work in the future. The results presented in our study correlated with other existing reports. The research showed that there is a decline in interests among young people to consider nursing as a future profession. This situation is directly related to: the specific work environment, low pay and too much responsibility.